The role of cow milk in reducing the number of streptococcus mutans - Irene E. Rieuwpassa; Donald R. Nahusona; Indah Ramadhani (Journal of Dentomaxillofacial Science, 2018)
Objective: This research aims to provide an overview of chewing gum casein effect on the number of bacteria streptococcus mutans and profile saliva. Casein is one of the elements in cow milk that has 70-80% of the total protein and function to prevent bacterium and other saliva sticking on the enamel surface of teeth. Consuming free sugar gum after eating can help to remineralise enamel, increase saliva and decrease the number of streptococcus mutans. Mouth work on mastication increases salivary flow rate. Therefore saliva production will increase and will change its acidity (pH).Material and Methods: The research design used was experimental research conducted in two groups where the control group by giving xylitol gum and the second group was given chewing casein gum. A total of 20 participants who match the criteria of research subjects chewed gum for 9 consecutive days and calculated the amount of streptococcus mutans, volume and pH of saliva.Results: The number of streptococcus mutans bacteria experienced a decline mainly in the group 69.60 in the first day to 22.80 in the ninth day. Thus, independent examination was done and p<0.005 was indicated, meaning that there was significant difference of casein gum in terms of decreasing streptococcus mutans bacteria, compared with xylitol gum.Conclusion: Casein gum made from cow milk can reduce the number of streptococcus mutans bacteria.